Solution Combustion Synthesis of Perovskite-type Catalysts for Diesel Engine Exhaust gas Purification. (2017) - chandra Dhal, Ganesh; Dey, Subhashish; Mohan, Devendra; Prasad, Ram
Abstract: Solution Combustion synthesis has been applied to LaFeO3 production with a view to boosting its activity for diesel engine exhaust gas purification by enhancing its specific surface area. With a highly exothermic and self-sustaining reaction, this oxide can be quickly prepared from an aqueous solution of metal nitrates (oxidisers) and urea (fuel). The favourable conditions for LaFeO3 formation were sought: only fuel-rich mixtures are effective, but carbonaceous deposits are formed when too much urea is used. Under operating conditions in which the combustion synthesis reaction takes place, the specific surface areas were not dramatically higher than those obtained with traditional methods; moreover, even short thermal treatments have been found to rapidly deactivate the catalysts by rapid sintering with a view to tackling these problems, NH4 NO3 was chosen as an additive for its low costs, highly exothermic decomposition and also because it generates gaseous products only, without altering the proportion of the other elements in the catalysts. With ammonium nitrate, specific area was enhanced from 4 m 2 /g up to about 20 m 2 /g. A short thermal treatment at 900 °C partially deactivates also the NH4 NO3 -derived catalysts. It was found that NH4 NO3 -boosted mixtures produce materials whose activity, after a similar thermal treatment, is practically the same as the perovskites obtained by the "citrates" method. Combustion synthesis is though rather cheap-in terms of reactants employed and quick, because the process requires few minutes at low temperature without successive calcination. However, the main drawback of this method is that hazardous or polluting compounds are emitted during the synthesis (mainly NH3 or NOX ).